Value and wastes in manufacturing. an overview and a new perspective based on eco-efficiency - Alberto Simboli; Raffaella Taddeo; Anna Morgante (Administrative Sciences, 2014)
In the last century, the evolution of manufacturing was characterized by several innovations, concerning technologies, processes, but also entire production systems, with radical changes in strategies, product design, and management of organizations. Cost, time, and quality are the pillars on which was based the industrial competitiveness during that era. In the most recent years, a renewed interest in environmental issues and socio-ethical values has gradually promoted the transition towards the so-called low impact economies. Producers are then required to pursue a more rational and eco-efficient use of resources and reduce production wastes to survive; also the concept of value chain has been often associated with the terms environmental/green or sustainable. Various studies have been carried out to encourage companies in including the environment in their strategic and operational decisions making. Industrial Ecology (IE) represents the latest and most ambitious attempt to reach this goal; however, a great deal of work remains to be done to achieve this goal. As a result, enhancing companies to integrate efficiency and sustainable practices still has a long way to go. This study presents an overview on the evolutionary dynamics of manufacturing in the industrial age, and offers a discussion about the potential synergies in integrating IE approaches and tools in Lean Manufacturing, by introducing the environmental load as a further type of Muda; the systematic actions to reduce this waste can build up the basis for improving competitiveness through the eco-efficiency.
Keywords: 350; lean manufacturing; eco-efficiency; industrial ecology; muda; value; wastes